Effects of Ghutka on Semen Analysis: Observe the Effects of Ghutka on Semen Analysis in Male Patients Presenting with Infertility - Kaweeta Kumari, Nand Lal Dhomeja, Momy Gul, Nazia Hashim, Syeda Zain, Faiz Bakhtawar, Shaheen Zafar (Pakistan Journal of Medical & Health Sciences, 2023)
Background: To observe the effects of ghutka on semen analysis in male patients presenting with infertility. Methods: It was a descriptive observational study conducted at SIRM (Sindh institute of reproductive medicine) from April 2021 till july 2021. All males with history of primary or secondary infertility who presented at SIRM opd and who were habitual ghutka (all types) and niswar eaters were included in the study. All males with history of primary or secondary infertility taking recreational drugs other than ghutka were excluded. A total of 52 male patients with history of eating ghutka were analyzed for male infertility at Sindh Institute of Reproductive Medicines, at Karachi Pakistan. Data was collected on a formatted questionnaire after informed consent. The study was approved by Ethical review board. Statistical analysis was done using SPSS version 22. Results: As the results were evaluated, primary infertility with ghutka eating was 11 % while secondary infertility was found in 89%. Out of the total,23% patients were eating dry ghutka while 77% patients were wet ghutka eaters. Low Bmi was seen in 7%. Patients, high BMI in 25% males while in 60%, BMl was normal. Primary infertility was seen in 17% males who were wet ghutka eaters while it was found in 72% with dry ghutka. Only 11% males who were eating dry ghutka presented with secondary infertility. Sperm motility was low in 15% while it was normal in 85% males. Normal sperm morphology was seen in 39% while 61%. Had a normal morphology. Azoospermia was seen in 1% while teratozoospermia was seen in 33%. Asthenoteratozoospermia in 6%. While Normozoospemia in 25% was seen Conclusion: Ghutka. Addiction is a menace in our Society and its use on the rise. Many males and even females in Pakistan especially at Karachi are addicted to it. One of the greatest known hazards is Oral cancer and many are the sufferers. It has systemic effects and in males is responsible for infertility especially who are taking it for a long time. Keywords: infertility, ghutka, smokeless tobacco, males, habitual